2023
DOI: 10.1021/acs.iecr.2c04595
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Effect of Ionic Liquids and Quaternary Ammonium Salts on the Kinetics of Methane Hydrate

Abstract: This study investigates the kinetics of gas hydrate (methane gas) in the presence of Ionic Liquids (ILs) and organic Quaternary Ammonium Salts (QASs). Aqueous solutions of eight ILs (five aromatic ILs and three aliphatic ILs) and three QASs have been studied for the kinetics of methane hydrate formation. In this study, five aromatic-based ILs with cations, viz., 1-hexyl-3methylimidazolium, 1-butyl-3-methylimidazolium, and 1-octyl-3-methylimidazolium, and anions such as [Br] − , [Cl] − , and [HSO 4 ] − were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Ionic liquids (ILs), which are a type of organic salt, have been found to be effective in promoting gas hydrate formation. Several studies have reported that certain ILs, such as 1-hydroxyethyl-1-methylmorpholinium chloride [21], aromatic-based ILs [22], choline octanoate [23], and 1-ethyl-3-methylimidazolium hydrogen sulfate [24], promote methane hydrate formation. Interestingly, the promoting mechanism of ILs differs from that of surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs), which are a type of organic salt, have been found to be effective in promoting gas hydrate formation. Several studies have reported that certain ILs, such as 1-hydroxyethyl-1-methylmorpholinium chloride [21], aromatic-based ILs [22], choline octanoate [23], and 1-ethyl-3-methylimidazolium hydrogen sulfate [24], promote methane hydrate formation. Interestingly, the promoting mechanism of ILs differs from that of surfactants.…”
Section: Introductionmentioning
confidence: 99%